Merleau-Ponty e l’istituzione: la radice sociologica - Fortuzzi, Matteo (Studi Politici, 2022)
This article brings out the relation between Merleau-Ponty and the France sociology, which is crucial to understand Merleau-Ponty’s concept of institution. In particular, Merleau-Ponty’s debt to the work of Mauss, only partially brought to light by the philosopher himself, turn out to be decisive: Maussian themes such us corporeality, symbolism, institution, language, the theory of expression, identify a valuable space of research and analysis for the reconstruction and understanding, in the similarities and differences, of some of Merleau-Ponty’s most significant thesis, which precisely in the concept of institution find their vanishing point.